Geoenvironmental performance of nanogeopolymer-modified natural soil: Towards sustainable geocomposite liner application - Frank Ikechukwu Aneke; Denis Kalumba (Results in Engineering)
The inevitable desiccation crack and excessive swelling of expansive clays have necessitated optimizing clayey soils for leachate retention and long-term performance in the landfill. Most clays are not suitable for compacted clay liner (CCL) use. To improve these substandard clay materials against heavy metals contamination and leachate permeation into the substrate soil. A moderate alkali solution of sodium silicate/sodium hydroxide (alkaline activator ratio: 0.5) concentration of 10 M and nanosized slag was used to build a nano-geopolymer (NGP). The synthesis of NGP was achieved by blending the alkali solution with varying percentages of nano slag (5 %, 10 %, 15 %, and 20 %). The developed NGP was used to modify the CCLs, followed by experimental testing. The fabricated CCL specimens were subjected to a series of pH tests, cation exchange capacity tests (CEC.), compaction tests, swelling pressure tests, unconfined compressive strength (UCS) tests, hydraulic conductivity (HC) tests, and desiccation crack tests through a digital image analyzer to evaluate the geotechnical performance of the NGP treated CCL. The results revealed an average of 83 % increase in strength. Meanwhile, the surface crack area ratio decreased to 28 % upon 20 % inclusion of NGP content. On the other hand, as the percentages of NGP increased, the swelling pressure decreased from 550 kPa to 130 kPa while the hydraulic conductivity decreased from 2.6×10−8m/s to 2.1×10−10m/s, suggesting an improved clay liner with greater retention capacity. Furthermore, with 20 % of nano-geopolymer content, the composite liner met the required standards for liner construction, including hydraulic conductivity <10−9 m/s and UCS (0.9 MPa > 0.2 MPa). Including NGP in CCL significantly improved the geotechnical properties of natural in-situ soil, making the investigated natural soil a suitable baseliner for leachate retention in landfills.